Liminal scenarios of urbanity: The trunk stations of the Metropolitan of the City of Lima - Chavez Leonardo, Aroldo Kevin (2023)
The present text proposes to retake a classic concept of anthropology, the liminal or margin state, as a theoretical framework to analyze a contemporary scenario of the urbanity of the city of Lima: a rapid transit, urban, public and modern bus system, the Metropolitan. In this sense, this transport system will be understood as a stage of passage, bridge and transit that brings together various anonymous users who seek to reach their destination while interacting under collective pressure -such as neophytes or communitas who They seek to cross the threshold. For this, the analysis of various interaction scenarios that were registered will be used, the study of the two morphologies of the Metropolitan, as well as the results and analysis of 137 forms that were intended to support this text. In short, it will seek to understand the Metropolitan as a constant scenario of liminality of urbanity, reaffirming the non-decontextualization of rites of passage as a framework of analysis in contemporary urban places.